Effect of texting and handwriting on hand-grip and key-pinch strength among female-collegiate students: randomized controlled trial - El-gohary , Tarek Mohamed Fathi; Marwan Mahmoud Aljohani (Journal of the Pakistan Medical Association, 2023)
Objectives: To evaluate immediate and long-term effect of texting or handwriting on hand-grip and key-pinch strength among healthy female students. Method: The single-blind, randomised controlled trial was conducted between February and April 2021 after approval from the ethics review committee of the College of Medical Rehabilitation Sciences, Taibah University, Saudi Arabia, and comprised female Physio Therapy students aged 19-23 years who were right-hand dominant and had normal body mass index. The subjects used smartphones and electronic gadgets for >2hrs daily, writing more than 10min/day. They were randomised using sealed envelopes into five groups. Group A practised 10min texting, group B 15min texting, group C 10min writing, group D 15min writing, and group E used the phones only for talking or watching, with no texting or writing, and was taken as the control group. Hand-grip strength and key- pinch strength were assessed one minute before starting, and within one minute after having finished the assigned hand activity. All measurements were recorded in the sitting position using a single hand-grip dynamometer. Data was analysed using SPSS 23. Results: Of the 65 individuals assessed, 60(92.3%) were initially enrolled, but the study was finished by 50(83.3%) subjects with a mean age of 20.88±0.98 years and mean body mass index 20.8±2.30kg/m2. There were 12(24%) subjects in group A, 7(14%) in group B, 12(24%) in group C, 10(20%) in group D and 9(18%) in group E. The association of the time-based groups with hand-grip and key-pinch strength was not significant (p>0.05). Conclusions: Texting and handwriting did not have any significant immediate effect on hand-grip or key-pinch strength. Clinical Trial Number: (NCT04810416). Key Words: Hand-strength, Pinch-strength, Students, Text messaging, Writing.